2019
DOI: 10.15641/ghi.v2i1.728
|View full text |Cite
|
Sign up to set email alerts
|

Engaging minibus taxi drivers in the quest for child safer roads

Abstract: South Africa has double the world average child road fatality rate, with at least 1 300 children killed every year. A leading contributor to this public health challenge is the lack of safe public transport that enables children to reach schools easily. Minibus Taxis (MBTs), South Africa's incarnation of paratransit services, have aimed to fill this gap by providing transport at a reasonably priced fare and a relatively higher frequency, compared with other modes of public transport. However, the informal natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…In the current study, in keeping with the first author’s experience as a service provider, most participants reported that the public transport system was the only form of transportation they are using to take their children to the healthcare services, similar to other studies on disability and access in low- and middle-income countries (Aldersey et al, 2016; du Preez et al, 2019; Eseta, 2017; Ipingbemi, 2015; Janmohammed et al, 2019; Swartz, 2012, 2015, 2019; Tanser et al, 2001). In our study, while minibus taxis were available, participants describe access and experiences of using minibus taxis as difficult.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the current study, in keeping with the first author’s experience as a service provider, most participants reported that the public transport system was the only form of transportation they are using to take their children to the healthcare services, similar to other studies on disability and access in low- and middle-income countries (Aldersey et al, 2016; du Preez et al, 2019; Eseta, 2017; Ipingbemi, 2015; Janmohammed et al, 2019; Swartz, 2012, 2015, 2019; Tanser et al, 2001). In our study, while minibus taxis were available, participants describe access and experiences of using minibus taxis as difficult.…”
Section: Discussionsupporting
confidence: 78%
“…As in many other African countries, and in the absence of a well-functioning state-provided accessible transport system, many impoverished South Africans depend on minibus taxi services for their transport needs. These taxis have a poor safety record (Janmohammed et al, 2019) and present major challenges in terms of accessibility for people with a range of impairments, including mobility impairments and communication impairments (Green et al, 2015;Kett et al, 2020;Munthali et al, 2019;Swartz, 2019;Visagie et al, 2015).…”
Section: Equity In Healthcare Accessmentioning
confidence: 99%
“…Communities in SSA are faced with similar expectations. In South Africa for example, Winkler (2006) expressed the view that most of the country's socio-economic developmental needs could be achieved through an increased supply of energy. This, however, must be done within the parameters of safeguarding natural resources such as water, land and atmosphere.…”
Section: Contextual Developments On Wecc Nexusmentioning
confidence: 99%
“…Hydropower is a trusted technology with signi cant potential in SA (White, 2011). It is a form of clean renewable energy making use of the available ow or head in water without consuming or polluting the water itself.…”
Section: Hydrokinetic Applicability To South African Canal Systemsmentioning
confidence: 99%